PENERAPANMODEL LEARNING CYCLE (LC ) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV A SDN21PEKANBARU - Neri Eriani Eriani; Mahmud Alpusari Alpusari; Otang Kurniaman Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :The problem onthis research is that low student’sscience learningoutcomes,this seen from average is 68,47. From 36 students who achieve Minimum Criteria for completeness is 16 students (44,44%),and students who notachieve Minimum Criteria for completeness is 20students (55,56%), minimun completeness criteria of SD Negeri 21 Pekanbaru is 70. Based on these problems need to be done to implement the action research model of Learning Cycle (LC). Thisresearch toimprove learning outcomesgradeIVAof SDN21Pekanbaru in academic year of2014/2015with 36students, the consisting of 16 male’sand 20 female’s.This research was done in three cycles. First cycle consists of two meetings with one daily test and cycle II consists of two meeting with one daily test and cycle III consists of two meeting with one daily test. Percentage of completeness in basic score was 44,44% with average is 68,47 and it changed into 66,67% with average is 73,44 in the first cycle, and the second cycle increased to 77,78% with average is77,55, and the third cycle increased to 88,89% with average is 85.The percentage of teacher activity also increased, this seen from the percentage of all teachers in the first cycle of 73,75% increased to 83,75% in the second cycle, and increased again in the third cycle is 93,75%. The percentage of student activity also increased from 73,75% in the first cycle increased to 82,5% in the second cycle and increased again to 93,75% in the third cycle. From the above explanationit can be concludedthatthrough the application ofLearning Cyclemodels, canimprove learning outcomesIVAgrade science studentsat SDN21Pekanbaru in academic 2014/2015. Keywords: Application ofModelLearning Cycle(LC), StudentsLearning Outcomes